Letter: functional dyspepsia is associated with duodenal eosinophilia in an Australian paediatric cohort—methodological issues to avoid misinterpretation. Issue 3 (4th July 2017) - Safiri, S.; Ayubi, E.
Abstract : Linked Content This article is linked to Wauters et al papers. To view these articles visithttps://doi.org/10.1111/apt.14045 andhttps://doi.org/10.1111/apt.14178 .